Advances in laboratory diagnostic methods for cerebrospinal fluid testing for neurosyphilis - Gao, Zheng-Xiang; Gou, Yu; Liu, Xiao-Qin; Peng, Lei-Wen (Frontiers in Public Health, 2022)
Neurosyphilis is a chronic infectious disease caused by the invasion of Treponema pallidum into the central nervous system. In recent years, with the increase in the latent syphilis infection rate, the incidence of neurosyphilis has gradually increased, the typical symptoms of neurosyphilis have decreased, atypical manifestations have increased, and the clinical manifestations have become increasingly diverse. Cerebrospinal fluid testing plays an important role in the diagnosis of neurosyphilis. In recent years, there have been many advances in cerebrospinal fluid testing. This review focuses on the current and potential laboratory indicators of neurosyphilis in cerebrospinal fluid, aiming to provide a reference for clinical application and ideas for future experimental research of neurosyphilis.